Notes on the epistles of St Paul - Lightfoot, Joseph Barber, 1828-1889 (Grand Rapids, MI Baker, 1980)
Contents : I and II Thessalonians, I Corinthians 1-7, Romans 1-7, Ephesians 1:1-14. Includes bibliographical references and index.
First published 1895.
Keywords: Bible. N.T. Pauline epistles -- commentaries